2015
DOI: 10.1037/xlm0000128
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating word frequency and predictability effects in reading: Evidence from coregistration of eye movements and EEG.

Abstract: Two very reliable influences on eye fixation durations in reading are word frequency, as measured by corpus counts, and word predictability, as measured by cloze norming. Several studies have reported strictly additive effects of these 2 variables. Predictability also reliably influences the amplitude of the N400 component in event-related potential studies. However, previous research suggests that while frequency affects the N400 in single-word tasks, it may have little or no effect on the N400 when a word is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
118
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(149 citation statements)
references
References 95 publications
22
118
9
Order By: Relevance
“…As stated by Dimigen et al (2011, p. 565), “the present data make it hard to conceive the measurable neural effects of predictability as being causal in some way for the emergence of behavioral effects, because the bulk of the predictability effects in ERPs only followed those in behavior”. Further to this, Kretzschmar et al (2015) confirm the temporal discrepancy of the predictability effect and reveal an even more drastic one: their manipulation of word frequency produces an expected effect on eye movement latencies but not on the amplitude or latency of the N400 (or any other) wave component. This runs counter to the assumption that any behavioral change can only arise as an effect of causal neural activity.…”
Section: Behavioral Effects Precede Neurophysiological Effectssupporting
confidence: 67%
See 1 more Smart Citation
“…As stated by Dimigen et al (2011, p. 565), “the present data make it hard to conceive the measurable neural effects of predictability as being causal in some way for the emergence of behavioral effects, because the bulk of the predictability effects in ERPs only followed those in behavior”. Further to this, Kretzschmar et al (2015) confirm the temporal discrepancy of the predictability effect and reveal an even more drastic one: their manipulation of word frequency produces an expected effect on eye movement latencies but not on the amplitude or latency of the N400 (or any other) wave component. This runs counter to the assumption that any behavioral change can only arise as an effect of causal neural activity.…”
Section: Behavioral Effects Precede Neurophysiological Effectssupporting
confidence: 67%
“…Recent co-registration studies of ERP and eye movements (Dimigen et al, 2011; Kretzschmar, Schlesewsky, & Staub, 2015) robustly report an earlier emergence of a word’s contextual predictability effect on eye movements (first fixation duration, average = 234 ms) than on brain activity (N400 peak latency = 384 ms; statistical onset of N400 latency = 248 ms). That is, at the timepoint when the peak amplitude of the predictability effect was reached in the ERP signal, 96% of fixations on the target word had already terminated; and 53% of fixations on the word had terminated before the onset of the N400 wave component.…”
Section: Behavioral Effects Precede Neurophysiological Effectsmentioning
confidence: 98%
“…Even when the ERPs showed a clear parafovea-on-fovea effect, EM measures in the present experiment were not sensitive to our experimental manipulation. This dissociation between both measures has been previously reported in sentence reading experiments (see Kretzschmar et al, 2015 for further discussion). However, it is important to note that the EM measures analyzed in the present study should be interpreted with caution, because they refer to fixations on the first word of a sequence, which involve different processes than those of words located in the middle of a sentence.…”
Section: Discussionmentioning
confidence: 70%
“…A similar situation is found when we compare studies that have applied coregistration methods to sentence reading. While one study reported a parafoveal N400 effect with highly constraining sentence contexts (Kretzschmar, BornkesselSchlesewsky & Schlesewsky, 2009), two other experiments in which word predictability was manipulated found a N400 modulation when target (n+1) words were fixated, but reported no parafovea-on-fovea effects on the pre-target (n) words (Dimigen et al 2011;Kretzschmar et al, 2015). Another study obtained concurrent EEG and EM measures in combination with the boundary paradigm described above (Dimigen, Kliegl, & Sommer, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation